2017
DOI: 10.2527/jas2017.1683
|View full text |Cite
|
Sign up to set email alerts
|

Genetic parameters for semen quality and quantity traits in five pig lines1

Abstract: We aimed to estimate genetic parameters for semen quality and quantity traits as well as for within-boar variation of these traits to evaluate their inclusion in breeding goals. Genetic parameters were estimated within line using a multiple-trait (4 × 4) repeatability animal model fitted for 5 pig lines, considering 4 semen traits: sperm motility (MOT), sperm progressive motility (PROMOT), log-transformed number of sperm cells per ejaculate (lnN), and total morphological abnormalities (ABN). The within-boar va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 22 publications
4
20
1
Order By: Relevance
“…For ABN, our estimates of heritability ranged from 0.15 ± 0.01 to 0.21 ± 0.02, which are well consistent with those (0.15 ± 0.05 to 0.25 ± 0.06) obtained by Marques et al. (). Instead of using individual ejaculate records, Smital et al.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…For ABN, our estimates of heritability ranged from 0.15 ± 0.01 to 0.21 ± 0.02, which are well consistent with those (0.15 ± 0.05 to 0.25 ± 0.06) obtained by Marques et al. (). Instead of using individual ejaculate records, Smital et al.…”
Section: Discussionsupporting
confidence: 92%
“…For MOT, our estimates of heritability (0.11 ± 0.02 to 0.42 ± 0.02) are slightly higher than those obtained by Marques et al. (), who reported estimated heritabilities of 0.08 ± 0.03 to 0.25 ± 0.05 in five pig lines (a synthetic line derived from the cross Large White and Pietrain, a Pietrain based line, a Duroc‐based line, a Large White‐based line and a Landrace‐based line), and are much higher than that (0.05) from Wolf (). For ABN, our estimates of heritability ranged from 0.15 ± 0.01 to 0.21 ± 0.02, which are well consistent with those (0.15 ± 0.05 to 0.25 ± 0.06) obtained by Marques et al.…”
Section: Discussioncontrasting
confidence: 85%
See 2 more Smart Citations
“…All the recommended steps for the GWAS method used were performed in each study and reliable candidate genes with biological meaning were found. In addition, Marques et al [ 42 ] reported high genetic correlations between MOT, PROMOT and ABN, which corroborate our findings regarding the overlapping QTL regions that explained more than 1% of the genetic variance for these traits. Therefore, we believe that the QTL results of the present and previous studies should not be considered as false positives and we conclude that the single-SNP method with pseudo-phenotypes and the amount of data in the previous study were not able to identify some of the relevant QTL related to MOT.…”
Section: Discussionsupporting
confidence: 91%